The cross-border strategies of European banks: Effects on performance - JESSY TROUDART; ERIC LAMARQUE (Bankers, Markets & Investors, 2017)
Are the cross-border strategies of European banks effective? Over the period from 2007 to 2012, banking systems experienced some important transformations in several dimensions including the international expansion, especially in OECD countries. However, European banks further continued their trend of increased foreign bank ownership between 2007 and 2012. Besides, the share of foreign banks assets in European area remains the same before and after the crisis in 2012 (about 80 % according to the report of the IMF in 2013). This is mainly due to the regionalization context in which European banks operate. Therefore, this paper is motivated by an intense internationalization in the banking sector from the beginning of this century until 2012. After five years of consolidation of equity capital and bank stability, many banks consider now again the opportunity to go abroad. We investigate whether the various options for expanding overseas have a positive impact on the profits of European banks. We analyse the results in which 42 European banks might expect expansion abroad though subsidiaries, conducting cross-border acquisitions, or forming cross-border partnerships, during the period 2004–12. We find that extending international operations through subsidiaries could have a negative impact on profits, whereas cross-border partnerships could improve them.